The responses of hospital nurses in Ireland and Southern Italy to the rationalisation of public health care, 1985-2000 - Pratschke, Jonathan (Trinity College (Dublin, Ireland). Department of Sociology, 2004)
This thesis seeks to address three interrelated research questions regarding changes in the funding, organisation and management of the health service in the Republic of Ireland and Southern Italy over the past two decades. The first question regards the extent to which health service rationalisation has followed a similar pattern in Ireland and Italy, the second asks what impact this process has had on nurses’ working conditions and the third inquires about how the nursing unions have responded. The comparative framework for the research is based on an extension of Esping-Andersen’s typology of welfare regimes.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin